Reimbursement process of medicinal products in Poland and in the world - Aneta Katarzyna Mela (Farmacja Polska, 2020)
Reimbursement of drugs is a complex process which requires consideration and balancing of interests of various parties: patients, pharmaceutical manufacturers and payers financing medical services. Poland is an example of a country where no medicine is reimbursed without formal procedures. It is not possible for a drug to be reimbursed in a new medical indication, without an assessment of health technologies. Following the example of other developed countries, Poland in 2005 introduced a health technology assessment system to the drug reimbursement process by establishing an advisory body for the Minister of Health - the Agency for Health Technology Assessment, which tasks include in particular, developing recommendations regarding the financing of health technologies. This article aims at presenting approaches to reimbursement of drugs in the following countries: Poland, United Kingdom, France, the Netherlands, Germany and Canada. Reimbursement process is diverse depending of conditions in particular country. Various approaches are present in terms of: reimbursement of drugs used in hospital and available in pharmacies, generic and innovative drugs, time for which reimbursement decision is issued as well as method of accounting for expenditure for drugs and possible replacement of drugs with cheaper substitutes. In each of the presented countries one can note differences and similarities in terms of: institutions engaged in reimbursement process, significance of assessment and recommendations issued by appropriate institutions, treatment assessment criteria, approach to innovative and generic drugs, instruments used in order to minimize payer’s cost and maximize patients’ access to treatment, actions aiming at unifying financing among particular groups of drugs and general complexity of the whole reimbursement process.